Compound Vortex Metalens with Linearly Polarized Encryption. Issue 2 (12th January 2023) - Zhou, Changda; Lu, Peiyao; Yue, Zhiyuan; Xu, Jilian; Teng, Shuyun
Abstract: In view of the rapid development of nano‐fabrication technology and the wide application of composite vortex fields, a kind of compound vortex metalens with polarization encryption is proposed. The proposed compound vortex metalens can simultaneously generate compound vortex beams with double annular strengths, unequal topological charges, and specific polarization states in different radial regions, which have the characteristic of higher dimensional singularity. The compound vortex metalens consisting of rectangular nanoholes works under linearly polarized light illumination, and the topological charges of the generated compound vortex beam can be modulated through rotating nanoholes. Simulation results and theoretical analysis verify the reliability of polarization‐coded compound vortex beam metalens. The variation of polarized encrypted transmission field with the incident polarized angle shows the broader performance of polarization encryption compound vortex metalens. The multiple singularities and polarization encryption properties of the generated compound vortex beams combining with the integrated metasurface will be helpful for broadening the applications of singular beams. Abstract : Here, a compound vortex metalens is proposed, which can simultaneously generate compound vortex beams with multiple annular intensities, topological charges, and specific polarization states in different radial regions. These compound vortex beams have high dimensions singularity. The two encryption factors significantly improve the information security and the multi‐topology of the compound vortex beam also increases the encrypted information capacity.